SPERM MORPHOLOGICAL ABNORMALITIES IN ASTHENO OLIGOSPERMIC FRIESWAL BULLS
Eighteen mature Frieswal (Holstein Friesian X Sahiwal; having 5/8 exotic inheritance) bu/ls of similar age (29.79±0.90 months) were divided into 2 categories i.e. poor (N=9, sperm motility< 50% and concentration <600 million/ml) and normospermic bulls (N=9). Sperm viability and morphology was evaluated by eosin, nigrosin staining technique. The mean (±SE) number of total viable, morphologically normal and progressively motile sperm (in millions) per ejaculate in poor bulls (1234.53±266.96, 636.21 ±150.18 and 272.22±68.06, respectively